Cortisol Levels in Childhood Associated with Emergence of Attenuated Psychotic Symptoms in Early Adulthood. (September 2021) - Cullen, AE.; Fisher, H.L.; Gullet, N.; Fraser, E.R.; Roberts, R.E.; Zahid, U.; To, M.; Yap, N.; Zunszain, P.A.; Pariante, C.M.; Wood, S.J.; McGuire, P.; et al.
Abstract : Background: In youth at clinical high-risk for psychosis, cortisol elevations predict transition to psychosis, but it is unclear whether cortisol alterations are evident at an earlier clinical stage. We investigated whether cortisol levels and stressors in childhood were associated with later attenuated psychotic (AP) symptoms. Methods: A sample of children (N=109) enriched for psychosis risk factors were recruited at age 9-12 years and assessed at age 11-14 years (T1) and 17-21 years (T2). Measures of psychopathology, psychosocial stressors, and salivary cortisol were obtained at T1. AP symptoms were assessed at T2. Results: Diurnal cortisol (β = 0.915, 95% CI: 0.062, 1.769) and daily stressors (β = 0.379, 95% CI: 0.034, 0.723) at T1 were independently associated with AP symptoms at T2 after accounting for demographic factors and T1 psychopathology. Exploratory analyses indicated a significant interaction between diurnal cortisol and daily stressors (β = 0.743, 95% CI: 0.081, 1.405), with the highest predicted T2 AP symptoms occurring when both were increased. Conclusion: Daily stressors and diurnal cortisol elevations during late childhood (a neurodevelopmentally vulnerable time-period) confer risk for developing AP symptoms.